Climate change worry in the times of the COVID-19 pandemic. Evidence from two large-scale European surveys - Ádám Stefkovics; Csilla Ágoston; Emőke Bukovenszki; Andrea Dúll; Olivér Hortay; Attila Varga (Climate Risk Management, 2024)
Climate change beliefs drive individual actions tackling climate change and influence the support of climate change policies. In the last two years, however, humanity has faced a parallel global crisis: the COVID-19 pandemic. The widely communicated finite pool of worry theory suggests that consideration of a crisis usually decreases when another crisis is emerging. Nevertheless, according to recent evidence, climate change concerns or awareness have increased during the pandemic. In this study, we aimed at describing recent changes in climate change concerns and examining the effect of COVID-fear on climate change worry in 28 European countries drawing on data from nationally representative surveys. We observed a strong increase in climate change concerns between 2016 and 2021, and a slight additional increase between during the pandemic (between 2020 and 2021) in the 28 countries examined, especially in those countries, where the level of concern was originally lower. The results of the multilevel models showed that COVID-19 fear reinforces climate change concerns which contradicts the finite pool of worry theory. These findings may come as good news given that increasing climate change concerns may raise individuals' support of climate policies, however, carefully designed awareness-raising campaigns are needed.